Peningkatan Partisipasi Umat dan Pelayanan Gereja kepada Umat Paroki Hokeng Melalui Kegiatan KKN Mahasiswa STP Reinha Larantuka, Wolorona Barat - Sogen, Vinsensius Florianus Dalu; Watun, Valentina Ina Abong; Keban, Yosep Belen (Abdibaraya, 2023)
The activities of Dedication to the Society (PkM) in the Parish of the Queen of the Holy Land of Hokeng are carried out because these days the participation of the people in the life of the church is decreasing and the service of the Church to the people is also becoming less and less noted. The purpose of these activities is to improve the service of the Church to the people because the Church service is still limited and is not able to reach the entire community of the parish of Sta. Maria Queen of the Universe of Hokeng. As for the Method of the Church's activities in the Parish of the Queen of the Universe, the Archdiocese of Larantuka is a Live-in method that emphasizes the participation of the people in every activity. The investigation began with field observation activities by the students, after which a three-day supply operation was carried out. The result of this activity is that the people of this parish are well aware of the duty and responsibility of helping to give momentum in the work and responsibilities of being a believer and a witness to Christ. Many of the activities carried out with C.C.E. students can have a good impact on all the congregations, and they are increasingly enthusiastic to carry out the Church's task. Keywords: participation of the people; Dedication to the Society; Church Service